ZADANIE JAKO FORMA WSPIERANIA REFLEKSYJNEGO NAUCZANIA GRAMATYKI - Janowska, Iwona; Rabiej, Agnieszka (Neofilolog, 2019)
The paper discusses the issues of form-focused instruction in foreign language pedagogy with the special emphasis on the task-based language teaching. There is a growing realization among the researchers and the language educators that the formal aspects of the target language need to be incorporated into the language teaching in order to facilitate the learners’ in achieving high levels of accuracy as well as communicative effectiveness. The authors point out to different techniques and procedures that are used in task-based language teaching to stimulate learners’ reflection on the formal aspects of the target language and to develop their capacity of noticing the linguistic forms as they are engaged in meaning focused activities.